Exploring How Personal and Environmental Factors Influence Stress Levels Among Chinese Students: The Moderating Effect of Chinese Painting Experience - He Binnge; Ooi Boon Keat (Sociological Research And Innovation, 2025)
The current study explores how personal and environmental factors affect stress levels of students, while also investigating the moderating effect of Chinese painting experience on the relationship between stressors and students' stress levels. Online and self-administered surveys were utilized to collect data from 384 respondents in Shandong Province, China. Data analysis was conducted using SPSS and Smart PLS. The findings revealed a positive correlation among the variables and also shows the moderating effect of Chinese painting experience among them. Theoretical implications, along with identified research gaps in the literature, highlighted a culturally inclusive framework. Findings suggested that engaging in Chinese painting provides mental peace, reduces stress levels, and fosters professional growth among students. Given the rising prevalence of stressors among students, universities should consider implementing Chinese painting experience classes. Such classes have been shown to alleviate stress and promote physical fitness. Hence, it was concluded that culturally relevant artistic practices, for instance Chinese painting, effectively alleviate stress and can inform mental health strategies for students in high-pressure academic settings